Analysis of Two Cosmid Clones from Chromosome 4 of Drosophila melanogaster Reveals Two New Genes Amid an Unusual Arrangement of Repeated Sequences - Locke, John; Podemski, Lynn; Roy, Ken; Pilgrim, David; Hodgetts, Ross (Genome Research, 1999)
Chromosome 4 from Drosophila melanogaster has several unusual features that distinguish it from the other chromosomes. These include a diffuse appearance in salivary gland polytene chromosomes, an absence of recombination, and the variegated expression of P-element transgenes. As part of a larger project to understand these properties, we are assembling a physical map of this chromosome. Here we report the sequence of two cosmids representing ∼5% of the polytenized region. Both cosmid clones contain numerous repeated DNA sequences, as identified by cross hybridization with labeled genomic DNA, BLAST searches, and dot matrix analysis, which are positioned between and within the transcribed sequences. The repetitive sequences include three copies of the mobile element Hoppel, one copy of the mobile element HB, and 18 DINE repeats. DINE is a novel, short repeated sequence dispersed throughout both cosmid sequences. One cosmid includes the previously described cubitus interruptus(ci) gene and two new genes: that a gene with a predicted amino acid sequence similar to ribosomal protein S3a which is consistent with the Minute(4)101 locus thought to be in the region, and a novel member of the protein family that includes plexin and met–hepatocyte growth factor receptor. The other cosmid contains only the two short 5′-most exons from thezinc-finger-homolog-2 (zfh-2) gene. This is the first extensive sequence analysis of noncoding DNA from chromosome 4. The distribution of the various repeats suggests its organization is similar to the β-heterochromatic regions near the base of the major chromosome arms. Such a pattern may account for the diffuse banding of the polytene chromosome 4 and the variegation of many P-element transgenes on the chromosome.